Tren Pengembangan Ilmu di Universitas Islam Negeri Maulana Malik Ibrahim Malang - Muslih, Mohammad (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2016)
It has been over a decade, in which the journey of State Islamic University (UIN) Malang in developing new scientific paradigm has appeared to be quite successful, particularly in establishing and developing an ?image? of Islamic-based sciences in their new forms. The success can be observed from, among other, people?s demand?from various segments of the society?to a number of books written by the lecturers of UIN Malang. Such tremendously remarkable achievement becomes certainly a worthy matter to observe and discuss, especially from the Philosophy of Science?s point of view concerning on how the pattern of scientific development?as a part of academic traditions?built by this Islamic higher educational institution. This article finds an important information that the development of science in UIN Malang has arrived upon the development of new theories and concepts, by placing al-Qur?ân and al-Sunnah as its main and fundamental foundations. It can be generally observed that there has been a sort of a pattern of ?Quranic justification? to the sciences developed by UIN Malang. It means that any scientific activity is intended to prove the ?scientificness? of al-Qur?ân. It has been also assumed, moreover, that al-Qur?ân is the book of science.